Application of the Duty not to Cause Significant Harm in the context of the Nile River Basin - Mengesha, Zewdu (Bahir Dar University Journal of Law, 2022)
The duty not to cause significant harm is an obligation of customary international law relating to utilization of international watercourses. This duty requires a state sharing freshwater resources to refrain from causing significant harm to other states through its use of a shared international watercourse. It also requires consideration of all relevant factors that are essential for its effective implementation in any given international watercourse. In relation to this duty, the Nile Basin States adopted the Nile Basin Cooperative Framework Agreement to regulate the use, development, protection, conservation and management of the Nile River Basin and its resources. However, the Nile River Basin Cooperative Framework Agreement did not set out detailed guidelines on how the Nile River Basin Commission should promote and facilitate the implementation of the principles enshrined under this Framework convention, which includes the duty not to cause significant harm. This entails drawbacks for the application of the principle in the Nile Basin. Thus, this Article examines how the duty not to cause significant harm should be applied in the Nile Basin.